Pengaruh Pengetahuan Pajak,Pelaksanaan Relawan Pajak Dan Motivasi Karir Terhadap Minat Berkarir Mahasiswa Akuntansi Di Bidang Perpajakan - Yentina Siregar; Maria Silitonga; Hendri Jaya; Artiani Lestari Tiurmaida Manalu (Universitas Riau Kepulauan, 2024)
Abstract. This study's overarching goal is to dissect the impact of factors including tax literacy, tax volunteerism, intrinsic drive, and interest in taxation as a profession.When analyzing data, one may check for a correlation between two variables by using multiple linear regression. Knowledge of taxes significantly affects interest in a tax-related profession, according to the data. Furthermore, tax volunteers help increase interest in taxes as a profession.There was also a strong correlation between professional drive and a desire to work in taxes. Implications for future study and practice include raising awareness of tax issues, promoting tax-related volunteer work, and inspiring people to seek out tax-related job opportunities.